Extensive Listening-while-reading: A Case Study applying the Minimalist Approach - John, Divya (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This paper is based on the concept of extensive listening-while-reading. It is an attempt to assist ‘vernacular-medium learners’ of English (i.e., learners whose medium of instruction is their mother tongue) to develop their listening skills in English by concentrating simultaneously on listening and reading. The study tries to prove the effect of the minimalist approach on the listening skills of the learners. The minimalist approach consists in indulging in at least a minimum listening input to reap maximum advantage. The experiment pattern comprises listening to an episode of the 6-minute English podcasts provided by the BBC Learning English website daily; reading aloud the same transcript along with the BBC presenter; recording the reading of one of the podcasts every week, and emailing it to the teacher. The study involves five vernacular-medium students though only one case is particularized herein. Our conclusion is that the students’ listening comprehension skills improved gradually.